Economic Integration In ECOWAS: 40 Years After - Michael P. Okom (European Scientific Journal, ESJ, 2016)
The Economic Community of West African States (ECOWAS) was launched in Lagos on 28 May, 1975, amidst fanfare and big dreams of economic nirvana: economic integration, development and prosperity. The template for the institutional mechanisms and infrastructure for the realization of the dreams were encapsulated in the Treaty itself and the relevant Protocols. The legal and institutional framework presented a picture perfect structure which only needed concerted and focused action, to realize ECOWAS’ lofty goals and objectives. 37 years after, this still remains a mirage. This paper examines the cause for this untoward status-quo and proffers ideas as to how the drive towards the actualization of the ECOWAS as a viable, virile, economic bloc can be attained.